The effect of principal supervision competence and teacher motivation on teacher performance in primary schools - Nurhasyim Nurhasyim; Yasir Arafat; Dessy Wardiah (JPGI (Jurnal Penelitian Guru Indonesia), 2021)
This study aims to m engetahui and describe the effect of the competence of supervising principals on teacher performance in SD Negeri Muara Telang, m e Knowing and describe the influence of teacher motivation on the performance of teachers in public primary schools Muara Telang, and Knowing and describing the effect of the competence of supervising principals and teacher motivation together on teacher performance in SD Negeri Muara Telang District . This research uses quantitative methods . The study population was all teachers at SD Negeri Muara Telang and the sample was obtained as many as 86 respondents . Data collection techniques using questionnaires, observation, and documentation. Data were analyzed by using linear regression formula is simple and multiple linear regression with SPSS . From the results of this study concluded that k Competency Supervision Principal affect the performance Elementary School Teachers in Muara Telang. Teacher motivation has an effect on teacher performance in primary schools in Muara Telang district . Principal Supervision competence and teacher motivation jointly influence teacher performance in SD Negeri Muara Telang District.